The Yeast Spindle Pole Body Component Spc72p Interacts with Stu2p and Is Required for Proper Microtubule Assembly - Chen, Xiaoyue Peter (The Rockefeller University Press, 1998)
We have previously shown that Stu2p is a microtubule-binding protein and a component of the Saccharomyces cerevisiae spindle pole body (SPB). Here we report the identification of Spc72p, a protein that interacts with Stu2p. Stu2p and Spc72p associate in the two-hybrid system and can be coimmunoprecipitated from yeast extracts. Stu2p and Spc72p also interact with themselves, suggesting the possibility of a multimeric Stu2p-Spc72p complex. Spc72p is an essential component of the SPB and is able to associate with a preexisting SPB, indicating that there is a dynamic exchange between soluble and SPB forms of Spc72p. Unlike Stu2p, Spc72p does not bind microtubules in vitro, and was not observed to localize along microtubules in vivo. A temperature-sensitive spc72 mutation causes defects in SPB morphology. In addition, most spc72 mutant cells lack cytoplasmic microtubules; the few cytoplasmic microtubules that are observed are excessively long, and some of these are unattached to the SPB. spc72 cells are able to duplicate and separate their SPBs to form a bipolar spindle, but spindle elongation and chromosome segregation rarely occur. The chromosome segregation block does not arrest the cell cycle; instead, spc72 cells undergo cytokinesis, producing aploid cells and polyploid cells that contain multiple SPBs.